DAMPAK PENGGUNAAN SMARTPHONE TERHADAP PERILAKU SISWA DI MA AL-MARFUIYAH - Devina, Putri; Kue, Marisa; Nugraha , Deri (Jurnal Citra Pendidikan, 2024)
ABSTRACT Smartphone use by students has a significant impact on their behavior. Even though it provides fast access to information and communication, excessive use can result in disruption in learning concentration, decreased productivity, and the potential for technology dependence. Additionally, in-person social interactions may be impacted, with the potential for isolation and lack of engagement in offline activities. The importance of a balanced approach and understanding its appropriate use needs to be considered in supporting student development. Students' smartphone use can have a significant impact on their behavior. Even though it provides fast access to information and technology, excessive use can cause interference in learning concentration, lack of direct social interaction, and potential misuse of time with less productive activities. In an educational context, it is important to understand how smartphone integration can impact a student's overall development